Raphaela Heil, Document Image Processing for Handwritten Text Recognition: Deep Learning-based Transliteration of Astrid Lindgren’s Stenographic Manuscripts - Jacob Orrje (Barnboken: Tidskrift för Barnlitteraturforskning)
Review/Recension